PROTOTIPE APLIKASI PENENTUAN TINGKAT KESEGARAN TEMPE BERBASIS CITRA DIGITAL - Angga Aditya Permana; Rifqi Riadhi; Desi Nurnaningsih (Universitas Muhammadiyah Tangerang, 2019)
Consumption level of tempe in Indonesia is higher than chicken and meat. Tempe freshness level we consume is an important indicator of tempe quality itself. A fresh diet will provide nourishment and energy to our body. Tempe freshness level can be determined using automated application that is synchronized with the mobile phones. This application prototype was constructed based on Matlab and digital image. A smart detection system of tempe which can detect the freshness of tempe was constructed to ensure whether tempe can be eaten or discarded. An application is developed to decide the good or bad quality of tempe through its freshness.Keywords: Digital image, freshness, Matlab, RGB, tempe